CRAB FISHING AND SOCIO-ECONOMIC CONSIDERATIONS IN LAGOS LAGOON SYSTEM IN NIGERIA - ADEOGUN, O. A; SOLARIN, B. B.; AMBROSE, E. E.; OGUNBADEJO, H. K.; BOLAJI, D. A.; ORIMOGUNJE, R. O.; AJULO, A. A.; OLUSOLA, A. O.; ARORIODE, R. O.; ADEOGUN, M. O. (Nigerian Journal of Fisheries, 2011)
A study was carried out to elicit information on the seasonal distribution, occurrence, economics of the crab fishery, and to inform discussions around potential fisheries management changes and reforms. Data analyses revealed that most of the crab collectors and fatteners were mainly Yorubas and Beninois. In the study area, over 90% crab collectors were within the age group of 21 – 60 years working age. Average fishing experience of crab collectors was 18.9 years. Literacy level showed that over 70% of the fishers could read, write and speak in English with 19% having no access to education. Peak season ranged from March to August. Catch per unit effort during the peak period was 25 – 60 kg/day/man. Crab collections are alternative sources of income and sustainable livelihood for the disadvantaged people in the Nigeria. There is a need for adequate information about the marketing system and performance for this export fishery product to increase the volume for local consumption and international export. The fishery does face some challenges, many of which are macroeconomic in nature, due to the high exposure the fishery has to the export market. These include exposure to fluctuations in export prices due to world supply, exchange rates, and growing emphasis on eco-certification for fishery products. In addition, the fishery faces pressures on earnings from a combination of rising fuel prices and stable prices.